The relationship between personality and cognition in older adults with and without early-onset depression - Armstrong, Megan; Kaufman, Jack; Maciarz, Jeremy; Sullivan, Daniel; Kim, Joseph; Koppelmans, Vincent; Langenecker, Scott; Weisenbach, Sara L. (Frontiers in Psychiatry, 2024)
It is well established that personality traits impact cognition, as certain personality factors are associated with performance in specific cognitive domains. However, the findings on the relationships between the Big Five traits and cognition are mixed. Additionally, few studies have explored these relationships in older adults with a history of depression. The present study aimed to (a) evaluate the impact of the Big Five personality traits in older adults with and without a lifetime history of depression; and (b) test the hypotheses that higher trait neuroticism would correlate negatively with cognitive performance, while openness to experience would correlate positively with cognition.Methods. The sample consisted of 138 participants between the ages of 55 and 78 (M = 65.56, SD = 6.36). Sixty-two participants met criteria for current or remitted Major Depressive Disorder, while 76 had no history of depression or other mental health disorders. Participants underwent comprehensive neuropsychological testing. Personality was assessed using the NEO Personality Inventory-Revised (NEO-PI-R), while depression status was determined using the Structured Clinical Interview for DSM-5 (SCID-5). Following a series of Pearson correlations of cognitive variables and the five personality factors, linear regression models were estimated for each significant correlation. Demographic variables (i.e., age, education and sex) were entered in block 1, depression status (never vs. ever) was entered in block 2, and the personality factor score, or sub-facet was entered in block 3.Neuroticism was not associated with cognitive performance on any outcome measure. The facets Openness to Feelings and Openness to Values were positively related to phonemic fluency. Further Openness to Values was positively related to cognitive flexibility. Discussion. Our results suggest that older people who are (a) more capable of identifying and understanding their feelings and the feelings of others, and (b) who are more willing to re-examine social, political, and religious values perform stronger on tasks measuring verbal fluency and cognitive flexibility, which are aspects of executive functioning. Interventions that aim to enhance open mindedness in older adults may have a parallel impact on improving executive functioning, though this would need to be examined prospectively.